FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERBANKAN SYARIAH - Ribut Sri Rahayu; Ari Dewi Cahyati (JRAK: Journal of Accounting Research and Computerized Accounting, 2014)
Objective of this study is to analyze how the implementation of Corporate Social Responsibility by using Index Islamic Social Reporting (ISR) on Islamic Banking in Indonesia and to examine how the influence of ShariaSipervisory Board (Dewan Pengawas Syariah – DPS), DPS conference, company size, profitability, leverage, andcommissioners on the disclosure of Corporate Social Responsibility (CSR) in Islamic banking in Indonesia.The method used is quantitative analysis. This study population is all Islamic banking in Indonesia during the period2011-2014. Samples are selected using purposive sampling method. Data analysis method used is multipleregression analysis. This research use secondary data from islamic banking annual report. Results of this study areall Islamic banking company has been doing CSR, size of the Sharia Supervisory Board, Sharia Supervisory Boardconference, Company Size and Leverage does not affect the disclosure of CSR in Islamic banking, while profitabilityhas a negative influence and board director has positive affect on disclosure CSR